Phosphorus and nitrogen-containing soybean oil polyols: Effect on the mechanical properties and flame retardancy of polyurethane foam - Oztaskin, Deniz; Yivlik, Lutfullah Yusuf; Acaroglu Degitz, Ilayda; Eren, Tarik (Tubitak Scientific & Technological Research Council Turkey, 2024)
In recent years, there has been an increasing interest in producing new materials that use renewable resources and halogenfree flame retardants with nonleaching properties. This research focuses on designing and synthesizing phosphorus -nitrogenbased biopolyols for use in polyurethane (PU) foam production. Polyol (ESBO-DYM) with dual functionalities, renewability, and nonflammability is synthesized through the epoxy ring -opening reaction of epoxidized soybean oil with phosphorus and nitrogencontaining tetraol products (DYM). The mechanical and flame retardant properties of PU foams with the addition of an ESBO-DYM were investigated. Increasing the amount of phosphorus in the PU foams increased the thermal stability properties. Using 100% ESBODYM as a polyol in the foam formulation increased the limiting oxygen index (LOI) value to 22.9% and resulted in the highest char yield according to the thermal gravimetric analysis (17% at 600 degrees C). Additionally, the introduction of ESBO-DYM polyol into the formulation resulted in a decrease in the compression strength of the foams. The foam density decreased as the amount of ESBO-DYM polyol in the formulation increased. The foam with the highest amount of ESBO-DYM had a foam density of 29.1 kg/m 3 . The morphology of the foams was characterized using a scanning electron microscope (SEM). As a result of this study, flame retardant polyurethane foams were formulated using a renewable source, polyol, along with commercial compounds.
Keywords: Epoxidized soybean oil; renewable resources; phosphorus; flame retardancy; polyurethane foam; THERMAL-DEGRADATION; POLYMERIC MATERIALS; EPOXY-RESINS; PLANT OILS; RECOVERY; TECHNOLOGY; BURDENS; DESIGN; Chemistry; Engineering